Siber suçlar sözleşmesinin getirdikleri ve iç hukuk açısından konuya yaklaşım - Akpek, Nusret Onur (İstanbul Bilgi Üniversitesi, 2015)
[Abstract Not Available]
Insights into the convention on cyber crime and the approach in terms of domestic law